Factor affecting public participation towards local government programs provided by Majlis Bandaraya Melaka Bersejarah (MBMB) / Amer Faezzudden Ahmad Fazal and Nadirah Harith - Ahmad Fazal, Amer Faezzudden; Harith, Nadirah (Faculty of Administrative Science and Policy Studies, 2011)
MBMB was the main factor in making Melaka a dynamic, progressive, and beautiful city. Its administration area has developed at the same rate with the overall development of Melaka where focus has been given towards the agricultural, industrial, and currently the tourism sectors. The infrastructural growth is very pronounced, comparable to any developed state in Malaysia. This condition has increased the rate of which investors have come to invest and therefore increase the number of jobs available. The purpose of this study was to examine the factors that determine public participation in Local Government of Majlis Bandaraya Melaka Bersejarah program.the factors relate to this study are tools of informations, channel of coomunications and capacity building.